A simple and efficient strategy for trace detection of ferroptosis-related miRNAs based on novel hydrophobic paper-based plasmonic substrate and “inverse molecular sentinel (iMS)” nanoprobes - Wang, Youwei; Chen, Bing; Fan, Jiang; Wang, Zhong (Frontiers in Bioengineering and Biotechnology, 2023)
Monitoring ferroptosis-related miRNAs is crucial for the treatment and prognosis of patients with intracerebral hemorrhage (ICH). In this work, a novel hydrophobic paper (h-paper)-based plasmonic substrate was produced by dropping DS Au nanorods with a narrow range of sizes and morphologies onto h-paper. Raman reporter molecules were adsorbed to the array surface, and surface-enhanced Raman scattering (SERS) spectra at randomly selected points reveal uniform and significant SERS enhancement. Hairpin DNAs (HPs) labeled with Raman reporters and hybridized with placeholder DNAs (“PHs”) were decorated on SERS substrate to fabricate SERS biosensor. Target miRNAs initiated the "inverse Molecular Sentinel" (iMS) process. During the process, PHs were removed and the conformation of HPs changed toward the hairpin structure, thus eliciting the proximity of Raman reporter to substrate and a stronger SERS signal. The proposed SERS biosensor performs well in terms of stability, reproducibility, and selectivity. The limits of detection (LOD) of miR-122-5p and miR-140-5p in serum were 4.17 aM and 4.49 aM, respectively. Finally, the fabricated SERS biosensor was applied to detect miR-122-5p and miR-140-5p in ICH patients and healthy subjects, and the results obtained by SERS were consistent with the results from quantitative real-time polymerase chain reaction (qRT-PCR), revealing the accuracy of the method. This simple, rapid approach offers great potential for the simultaneous detection of miRNAs in practical clinical applications